A)3(2y+5x)-2(3y-2x-1)+18=
b)-2(x-y+2)+3(2x+y-7)=
c)½(6-2x-4y)+8(x-½y+4)=
d)1½(4+6x-2y)+4(-x-y-1)=
e)5x-(2y+3x-6)+4y-(2x+y)=
f)-3x-2y+(8x-1½y+5)-½(x-y)=
g)8(4y-2x+3)-½(x+y)+6=
h)3/4(x-y+4)-2(x-1/4+5)=
i)0,2(x-2y+5)-0,4(x-y+7)=
j)0,7(2x-0,25y+8)-0,12(x-y+5)=

3

Odpowiedzi

2010-02-26T13:45:56+01:00
A)3(2y+5x)-2(3y-2x-1)+18=6y+15x-6y+4x+2=19x+2
b)-2(x-y+2)+3(2x+y-7)=-2x+2y-4+6x+3y-21=4x+5y-25
c)½(6-2x-4y)+8(x-½y+4)=3-x-2y+8x-4y+32=7x-6y+35
Najlepsza Odpowiedź!
2010-02-26T13:55:06+01:00
A)
3(2y+5x)-2(3y-2x-1)+18=
6y+15x-6y+4x+2+18=
19x+20

b)
-2(x-y+2)+3(2x+y-7)=
-2x+2y-4+6x+3y-21=
3y+4x-25

c)
½(6-2x-4y)+8(x-½y+4)=
3-x-2y+8x-4y+32=
35+7x-6y

d)
1½(4+6x-2y)+4(-x-y-1)=
6+9x-3y-4x-4y-4=
2+5x-7y

e)
5x-(2y+3x-6)+4y-(2x+y)=
5x-2y-3x+6+4y-2x-y=
y+6

f)
-3x-2y+(8x-1½y+5)-½(x-y)=
-3x-2y+8x-1,5y+5-0,5x+0,5y=
4,5x-3y+5

g)
8(4y-2x+3)-½(x+y)+6=
32y-16x+24-0,5x-0,5y+6=
31,5y-16,5x+30

h)
3/4(x-y+4)-2(x-1/4+5)=
0,75x-0,75y+3-2x+0,5-10=
-1,25x-0,75y-7

i)
0,2(x-2y+5)-0,4(x-y+7)=
0,2x-0,4y+1-0,4x+0,4y-2,8=
-0,2x-1,8

j)
0,7(2x-0,25y+8)-0,12(x-y+5)=
1,4x-0,175y+5,6-0,12x+0,12y-0,6=
1,28x-0,055y+5
2010-02-26T16:09:42+01:00
A) 3(2y+5x)-2(3y-2x-1)+18=6y+15x-6y+4x+2+18=19x+20
b) -2(x-y+2)+3(2x+y-7)=-2x+2y-4+6x+3y-21=4x+5y-25
c) ½(6-2x-4y)+8(x-½y+4)=3-x-2y+8x-4y+32=7x-6y+35
d) 1½(4+6x-2y)+4(-x-y-1)=6+9x-3y-4x-4y-4=5x-7y+2
e) 5x-(2y+3x-6)+4y-(2x+y)=5x-2y-3x+6+4y-2x-y=y+6
f) -3x-2y+(8x-1½y+5)-½(x-y)=-3x-2y+8x-1½y+5-½x+½y=4½x-3y+5
g) 8(4y-2x+3)-½(x+y)+6=32y-16x+24-½x-½y+6=31½y-16½x+30
h) ¾(x-y+4)-2(x-¼+5)=¾x-¾y+3-2x+½-10=-¼x-¾y-6½
i) 0,2(x-2y+5)-0,4(x-y+7)=0,2x-0,4y+1-0,4x+0,4y-2,8=-0,2-1,8
j) 0,7(2x-0,25y+8)-0,12(x-y+5)=1,4-0,175y+5,6-0,12x+0,12y-0,6=1,28x-0,055y+5